2020
DOI: 10.3389/fendo.2019.00917
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ART Calculator for Predicting the Number of Metaphase II Oocytes Required for Obtaining at Least One Euploid Blastocyst for Transfer in Couples Undergoing in vitro Fertilization/Intracytoplasmic Sperm Injection

Abstract: The ART calculator positive predictive values, i.e., the frequency of patients with at least one euploid blastocyst among those who achieved the estimated MIImin, were 84.8%, 87.5%, and 90.0% for 70%, 80%, and 90% predicted probabilities of success, respectively. The ART calculator effectively predicts the MIImin needed to achieve at least one euploid blastocyst in individual patients undergoing IVF/ICSI. The prediction tool might be used for counseling and planning IVF/ICSI treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Along these lines, the ART calculator -a clinical predictive model used to estimate the number of mature (metaphase II) oocytes needed to obtain at least one euploid embryo in couples undergoing ARTindicates that 13 (95% confidence interval [CI]: 11-16), 16 (95% CI: [13][14][15][16][17][18][19][20], and 19 (95% CI: 15-25) oocytes are needed for women aged 38, 39, and 40 years, respectively [10,11]. By contrast, only 5 (95% CI: 4-6) and 6 (95% CI: 5-7) oocytes are required for patients aged 33 and 34 years to have at least one euploid embryo [10,11]. These figures, combined with the proven reduced ovarian reserve in patients of advanced age, clearly indicate that reproductive outcomes will be decreased if treatment is further delayed.…”
Section: The Interpretation and Impact For Patients Undergoing Assistmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, the ART calculator -a clinical predictive model used to estimate the number of mature (metaphase II) oocytes needed to obtain at least one euploid embryo in couples undergoing ARTindicates that 13 (95% confidence interval [CI]: 11-16), 16 (95% CI: [13][14][15][16][17][18][19][20], and 19 (95% CI: 15-25) oocytes are needed for women aged 38, 39, and 40 years, respectively [10,11]. By contrast, only 5 (95% CI: 4-6) and 6 (95% CI: 5-7) oocytes are required for patients aged 33 and 34 years to have at least one euploid embryo [10,11]. These figures, combined with the proven reduced ovarian reserve in patients of advanced age, clearly indicate that reproductive outcomes will be decreased if treatment is further delayed.…”
Section: The Interpretation and Impact For Patients Undergoing Assistmentioning
confidence: 99%
“…iv. The ART calculator could be used to estimate the number of oocytes required to achieve at least one euploid embryo for transfer [10,11]. v. Personalizing the gonadotropin dose for ovarian stimulation and use of a GnRH antagonist protocol, followed by GnRH agonist triggering, and elective freezing of oocytes or embryos should be the first choice during this emergency period.…”
Section: Before Any Consultation Active Covid-19 Infec-mentioning
confidence: 99%
“… 26 , 27 Along these lines, recently, an online calculator was developed and validated based on predictive modeling to help in estimating the number of metaphase II oocytes required to obtain the Poseidon marker of success. 27 , 28 …”
Section: Poseidon Criteriamentioning
confidence: 99%
“…Secondly, and more importantly, the authors discuss embryo ploidy's intraindividual variation, which has relevance for patient counseling and treatment. Indeed, our studies show that there is variation in the probability of blastocyst euploidy within sameage women (2,7,8). To account for this variability, the ART calculator provides-in addition to the average minimum number of MII oocytes required for at least one euploid blastocyst-the 95% confidence interval of each estimation.…”
mentioning
confidence: 90%
“…Following its publication, the ART calculator was validated in a multicenter study involving approximately 1,500 infertile patients subjected to IVF-ICSI and PGT-A (7). The validation study showed that the estimations provided by the ART calculator were strongly correlated with the actual probability of blastocyst euploidy per MII oocyte (r = 0.91) and the minimum number of MII oocytes required to obtain at least one euploid blastocyst (r = 0.88).…”
mentioning
confidence: 99%